RNAi-based Boolean gates in the yeast Saccharomyces cerevisiae - Tian, Ximing; Volkovinskiy, Andrey; Marchisio, Mario Andrea (Frontiers in Bioengineering and Biotechnology, 2024)
Boolean gates, the fundamental components of digital circuits, have been largely investigated in Synthetic Biology because they permit building biosensors and carrying out biocomputing. In this work, a thorough study was conducted to design and construct, in the yeast S. cerevisiae, Boolean gates whose main component was the RNA interference pathway (RNAi), naturally absent from the budding yeast cells. We tested different expression cassettes for the siRNA precursor (a giant hairpin sequence, a DNA fragment-flanked by one or two introns-between convergent promoters or transcribed separately in the sense and antisense direction) and placed different components under the control of the circuit inputs (i.e., the siRNA precursor or proteins such as the Dicer and the Argonaute). We found that RNAi-based logic gates are highly sensitive to promoter leakage and, for this reason, challenging to be implemented in vivo. The convergentpromoter architecture turned out to be the most reliable solution, even though the overall best performance was achieved with the most difficult design based on the siRNA precursor as a giant hairpin.